Cancellation of a Certificate of Ownership Based on a District Court Decision in Tanah Datar District - Intan Mariska Aretra; Zefrizal Nurdin; Anton Rosari (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2023)
The problem formulations in this research are: the reason why the plaintiff did not submit a request for annulment to the BPN, the process of canceling a land title certificate based on a district court decision in Tanah Datar Regency, the status of the sale and purchase of land objects whose certificates are not valid but have not been canceled by the BPN, This research uses normative-empirical juridical methods. The reasons why the plaintiff did not submit an application for cancellation to the BPN were due to the plaintiff's ignorance of the cancellation procedure, physical control and certificates that were still controlled by the defendant, the length of the physical execution process due to resistance and the many requirements for submitting a cancellation to the BPN. 2. The process of canceling a certificate based on a court decision in Tanah Datar District begins with a request from an interested parties and then the file will be analyzed by the Land Office and then sent to the Regional Office, where the Regional Office will issue a decree of cancellation. 3.With the transfer of land rights by a person who is not the actual owner of the transferred land, his actions have clearly violated the principles that apply to land registration activities, namely the Nemo Plus Juris Principle and also the provisions of Article 1320 of the Civil Code, namely a lawful cause. Because the point of a lawful cause is violated, the agreement made by the parties becomes null and void.